EMPOWERING LIVES THROUGH EDUCATION: IMPROVING QUALITY OF LIFE FOR PEOPLE WITH TYPE 1 DIABETES IN PUNJAB (The Research of Medical Science Review, 2025)
Objective: This study aimed to evaluate the quality of life and identify factors influencing it among individuals with type 1 diabetes in Punjab. Additionally, it sought to gather their perspectives on the establishment of a national structured education program to empower people living with type 1 diabetes.Methods: A cross-sectional, questionnaire-based study was conducted. The findings revealed potential for improvement across all domains of health-related quality of life.Results: No statistically significant differences were observed across demographic and clinical subgroups of participants. Notably, 94.9% of respondents expressed support for the introduction of a structured education program for type 1 diabetes in Pakistan.Conclusions: There is a critical need for a comprehensive strategy to enhance awareness and understanding of type 1 diabetes in Pakistan.